Knowledge and Behavior of Traditional Vendors Regarding The Use of Borax (Sodium Tetraborate) in Cilok Snacks in The Taman Surawisesa Kawali Area - Iif Taufiq El Haque; Elis Noviati (Yayasan Inspirasi El Burhani, 2026)
Introduction: Food safety is essential for public health. However, some street foods still contain prohibited food additives such as borax, which can harm consumers, especially children Objective: The objective is to assess the level of knowledge and behavior of cilok vendors regarding the use of food additives, particularly borax, the use of which has been strictly prohibited by the government. Method: The approach taken in this study is “socio-legal research” due to its multidisciplinary or interdisciplinary nature, and thus includes case studies and field studies. The research was conducted in May 2026 with a population of cilok vendors in the Surawisesa Kawali park area, using total sampling of 16 individuals. ResultRegarding awareness of the ban on the use of borax, 14 cilok vendors (87.5%) were aware of it, while the other 2 vendors (12.5%) were not. Regarding compliance with the ban on the use of borax, 9 vendors complied, while the other 7 vendors did not. Conclusion: Education provided by officials to food vendors is crucial so that vendors can properly select and sort raw materials for production. Producers must recognize their responsibility—which goes beyond simply pursuing profit and prioritize the provision of safe food above all else. Food safety must be the guiding principle for producers, supported by government oversight and consumers’ ability to recognize the signs of unsafe street food.